Analysis of the immune response to Neospora caninum in a model of intragastric infection in mice - Teixeira, L. (2007)
To study experimental Neospora caninum infection initiated at the gastrointestinal tract, Toll-like Receptor 4- and functional IL-12Rbeta2 chain-deficient C57BL/10 ScCr mice were challenged intragastrically with 5 x 10(6) N. caninum tachyzoites. All parasite-inoculated mice eventually died with disseminated infection. In contrast, immunocompetent BALB/c mice challenged with 1 x 10(7) N. caninum tachyzoites by the intragastric (i.g.) or the intraperitoneal (i.p.) route remained alive for at least 6 months. Expansion of splenic B- and T-cells, the latter displaying both activated and regulatory phenotypes, and increased levels of IFN-gamma and IL-10 mRNA were detected in both groups of infected BALB/c mice compared with non-infected controls, whereas in the Peyer's patches only IFN-gamma mRNA levels were found to be increased. Parasite-specific IgG1, IgG2a and IgA antibody levels were elevated in the sera of all infected mice, whereas increased N. caninum-specific IgA levels were detected in intestinal lavage fluids of i.g. challenged mice only. These results show that N. caninum infection can be successfully established in mice by i.g. administration of tachyzoites. They also show that the immune response elicited in i.g. or i.p. infected BALB/c mice, although conferring some degree of protection, was not sufficient for complete parasite clearance.